2015
DOI: 10.1200/jco.2015.33.3_suppl.555
|View full text |Cite
|
Sign up to set email alerts
|

RacGAP1 expression, increasing tumor malignant potential, as a predictive biomarker for lymph node metastasis and poor prognosis in colorectal cancer.

Abstract: 555 Background: Rac GTPase activating protein (RacGAP) 1 plays a key role in controlling various cellular phenomena including cytokinesis, transformation and migration. Recently, the clinical significance of RacGAP1 expression has been reported in several malignancies. However, direct association between the RacGAP1 expression and colorectal cancer (CRC) has not been fully investigated. The aim of this study is to elucidate the function and clinical significance of RacGAP1 expression in CRC. Methods: The intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Overexpression of the complex members has also been correlated to a poor clinical prognosis in numerous types of cancers, including high-risk early breast cancer [13], hepatocellular carcinoma [14], gastric cancer [15], colorectal cancer [16] and melanoma for MgcRacGAP [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of the complex members has also been correlated to a poor clinical prognosis in numerous types of cancers, including high-risk early breast cancer [13], hepatocellular carcinoma [14], gastric cancer [15], colorectal cancer [16] and melanoma for MgcRacGAP [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a cytokinetic regulator, MgcRacGAP and the other members of the MgcRacGAP/MKLP1/Ect2 complex have been linked to human oncogenesis by controlling cell polarity [11] and driving epithelial-to-mesenchymal transition [12]. Overexpression of the complex members has also been correlated to a poor clinical prognosis in numerous types of cancers, including high-risk early breast cancer [13], hepatocellular carcinoma [14], gastric cancer [15], colorectal cancer [16] and melanoma for MgcRacGAP [17].…”
Section: Introductionmentioning
confidence: 99%
“…1B). Contrary to these data in gastric cancer, there was a recent report on upregulation of RACGAP1 in colorectal cancer with RACGAP1 being an independent predictive factor for prognosis [39]. However, a recent study on colorectal cancers demonstrated that the intracellular localization of the RACGAP1 protein dictates its relevance as prognostic predictor, with only nuclear staining indicating a poor prognosis and cytoplasmic staining actually resulting in a favorable outcome for the patient [40].…”
Section: Discussionmentioning
confidence: 88%
“…RACGAP1 (Rac GTPase-activating protein 1), a central spindle complex plays very important role in controlling various cellular process including cytokinesis, transformation, invasive migration and metastasis (Zhao et al, 2005). Previous studies identified the overexpression of RACGAP1 in gastric, ovarian, colorectal and several other cancers, implied its role in promoting tumor progression (Imaoka et al, 2015;Saigusa et al, 2015.…”
Section: Discussionmentioning
confidence: 99%